Multiple phosphorylations control recruitment of the KMN network onto kinetochores. Issue 12 (December 2018) - Hara, Masatoshi; Ariyoshi, Mariko; Okumura, Ei-ichi; Hori, Tetsuya; Fukagawa, Tatsuo
Abstract To establish a functional kinetochore, the constitutive centromere-associated network (CCAN) forms a foundation on the centromere and recruits the KMN network, which directly binds to spindle microtubules. The CENP-C and CENP-T pathways in the CCAN recruit the KMN network to kinetochores, independently. The CENP-C pathway has been considered the major scaffold for the KMN network in vertebrate CCAN. However, we demonstrate that it is mainly the CENP-T pathway that recruits the KMN network onto the kinetochores and that CENP-T–KMN interactions are essential in chicken DT40 cells. By contrast, less Ndc80 binds to the CENP-C pathway in mitosis and the Mis12–CENP-C association is decreased during mitotic progression, which is consistent with the finding that the Mis12 complex–CENP-C binding is dispensable for cell viability. Furthermore, we find that multiple phosphoregulations of CENP-T and the Mis12 complex make the CENP-T pathway dominant. These results provide key insights into kinetochore dynamics during mitotic progression. Hara et al. find that the recruitment of the KMN kinetochore protein network is mainly dependent on the CENP-T pathway and promoted by Cdk1-mediated phosphorylation of CENP-T in chicken DT40 cells.